Cerebellar tDCS Effects on Conditioned Eyeblinks using Different Electrode Placements and Stimulation Protocols - Beyer, Linda; Batsikadze, Giorgi; Timmann, Dagmar; Gerwig, Marcus (Frontiers in Human Neuroscience, 2017)
There is good evidence that the human cerebellum is involved in the acquisition and timing of classically conditioned eyeblink responses (CRs). Animal studies suggest that the cerebellum is also important in CR extinction and savings. Cerebellar transcranial direct current stimulation (tDCS) was reported to modulate CR acquisition and timing in a polarity dependent manner. To extent previous findings three experiments were conducted using standard delay eyeblink conditioning. In a between-group design effects of tDCS were assessed with stimulation over the right cerebellar hemisphere ipsilaterally to the unconditioned stimulus (US). An extracephalic reference electrode was used in experiment 1 and a cephalic reference in experiment 2. In both parts the influence on unconditioned eyeblink responses (UR) was investigated by starting stimulation in the second half of the pseudoconditioning phase lasting throughout the first half of paired trials. In a third experiment, effects of cerebellar tDCS during 40 extinction trials were assessed on extinction and reacquisition on the next day. In each experiment, 30 subjects received anodal, cathodal or sham stimulation in a double-blinded fashion. Using the extracephalic reference electrode, no significant effects on CR incidences comparing stimulation groups were observed. Using the cephalic reference anodal as well as cathodal cerebellar tDCS increased CR acquisition compared to sham only on a trend level. Analysis of timing parameters did not reveal significant effects on CR onset and peaktime latencies nor on UR timing. In the third experiment, cerebellar tDCS during extinction trials had no significant effect on extinction and savings on the next day. The present study did not reveal clear polarity dependent effects of cerebellar tDCS on CR acquisition and timing as previously described. Weaker effects may be explained by start of tDCS before the learning phase i.e. offline, individual thresholds and current flow based on individual anatomy may also play role. Likewise cerebellar tDCS during extinction did not modulate extinction or reacquisition. Future studies are needed in larger subject populations to determine parameters of stimulation and learning paradigms yielding robust cerebellar tDCS effects.